Cost Analysis of Construction Cost Planning for Landfill Site - Junaedi, Nurhayati; Bayuaji, Ridho; Susilo, Alfred Jonathan (Bina Nusantara University, 2025)
Accurate construction cost planning is essential to ensure project success, as inaccurate estimates may lead to delays, cost overruns, and reduced quality. Landfill construction, which is more complex than many other infrastructure projects, includes several components such as landfill work, leachate treatment facilities, and supporting infrastructure. The purpose of this study is to determine the major cost factors that have a major impact on the overall cost of building landfill sites. With the aid of SPSS software, a regression analysis was carried out using cost data from six landfill projects in Java Island that were completed between 2013 and 2018. With a Sig value of 0.000 (<0.05) and a very strong correlation (Pearson Correlation 0.991, within the 0.8–1.0 interval), the results show that landfill work (X3) significantly affects total costs (Y). Leachate treatment facilities (X4) are another crucial element in a number of situations, but landfill work (X3) consistently represents the largest portion of construction costs, according to proportion analysis. These results demonstrate the growing significance of environmental facilities and point to landfill work as the main factor influencing landfill construction costs. The study offers contractors and federal and local governments useful information for creating more precise cost estimates, maximizing budgetary allotments, and enhancing planning and development efficiency for landfill projects.